Geotourism: A Sustainable Development Alternative for Remote Locations in Western Australia? - Pforr, Christof; Dowling, R.; Newsome, D. (Springer, 2014)
Currently, Western Australia (WA) is experiencing its biggest ever mining boom in history with predictions about the resource sector underpinning the state’s economic development well into the future. Built on WA’s rich natural resources, the mining sector has traditionally been a pillar of any government’s economic policy, and indeed much of WA’s socio-economic history is associated with its mineral wealth, discoveries and exploitation. From a purely economic viewpoint WA’s landscapes are at times portrayed as not much more than a ‘big quarry’ to exploit, and undeniably, past and present mining and exploration activities have left visible and often irreversible scars scattered across Western Australia. The broader impacts of mining in the state will provide the requisite background in this chapter, which explores the potential of tourism as a sustainable development alternative in some locations with particular focus on the role of geotourism.